ECONOMIC GOVERNANCE AND PUBLIC FINANCE IN KAUTILYA'S ARTHASHASTRA - Rashid Manzoor Bhat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The study attempts to explore the Arthashastra, an ancient Indian treatise on public finance, authored by Kautilya around 300 BCE during the Mauryan period. The Arthashastra covers a wide range of topics including administration, politics, ecology, and economics, providing insights into the economic and political conditions of that era. The treatise emphasises the importance of treasury management, revenue generation, and expenditure allocation for the well-being of the state and its citizens. It enumerates seven sources of revenue, including income from crown property, state-controlled activities, taxes, trade, fees and service charges, fines, and miscellaneous sources. The Mauryan state, guided by the principles of the Arthashastra, established a centralised and efficient administration with specific officials responsible for revenue collection and management. The study also explores the significance of fraud prevention, accounting, auditing, and budgeting in public finance. The Arthashastra serves as a valuable historical document, offering inspiration and guidance for modern public finance, emphasising the balance between state management and the welfare of the people.